Mismatch of Subjective and Objective Risk of Falling in Patients with Dementia - Hauer, Klaus; Schwenk, Michael; Englert, Stefan; Zijlstra, Rixt; Türner, Sabine; Dutzi, Ilona (Journal of Alzheimer's disease, 2020)
Background: Match or mismatch of objective physiological and subjectively perceived fall risk may have serious consequences in patients with dementia (PwD) while research is lacking. Objective: To analyze mismatch of objective and subjective fall ris
Gesehen am 14.01.2021